Effect of the Innovative Running Shoes With the Special Midsole Structure on the Female Runners’ Lower Limb Biomechanics - Fu, Fengqin; Guo, Lianming; Tang, Xunfei; Wang, Jiayu; Xie, Zhihao; Fekete, Gusztáv; Cai, Yuhui; Hu, Qiuli; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2022)
To research the effects of innovative shoes on the biomechanics of the lower limbs and perceptual sensitivity in female runners. In this paper, fifteen healthy female runners were recruited to run through a 145m runway with planted force plates at one peculiar speed with two kinds of shoe conditions (Innovative shoes (IRS): a 16mm heel-toe drop with three layers of the midsole, Normal running shoes (NRS): regular jogging shoe) while getting biomechanical data. Perception of shoe characteristics was assessed simultaneously through a 15 cm visual analogue scale (VAS). The time series parameters were calculated by Statistical Parametric Mapping (SPM) technique. Regarding 0D parameters, the dorsiflexion angle ankle of IRS at touchdown, the peak dorsiflexion angle, range of motion (ROM), peak dorsiflexion velocity, and plantarflexion moment of IRS on the metatarsophalangeal joint (MTPJ) during running were significantly smaller than that of NRS (all p<.001). In addition, braking phase and the time of peak vertical force 1 of IRS were found longer than that of NRS (both p<.05). The SPM analysis exhibited a clearly higher ankle dorsiflexion angle for IRS compared to NRS between 0% and 4% of the stance time (p< .05). Bigger knee internal rotation angle for IRS than that of NRS from 0% to 6% and 63% to 72% of stance time (both p< .05) were also found, besides, the IRS reduced vertical GRF from 11% to 17% of the stance phase (p = 0.009) and braking anteroposterior GRF from 22% to 27% of the stance phase (p = .043) compared to the NRS. Runners were able to perceive the cushioning of IRS was better than that of NRS. This researching demonstrated that shoe drop impacts running biomechanical patterns like the previous research. Compared with normal running shoes, Innovative running shoes in this study could effectively improve the cushioning and propulsion performance, but the stability had not changed significantly. It would be benefit in the industrial utilization of shoes producers in light of the reducing the risk of running injuries.